Legal regulations for ships arriving in and/or departing from ports : achievements and open issues - Rukavina, Biserka (Array, 2020)
This paper gives an overview of the legal regulations on reporting formalities for ships arriving in and/or departing from ports, both on international and EU level, as well as about the solutions in the Republic of Croatia. In particular, there are analyzed the achievements of the International Maritime Organization (IMO), which represent the base for further action. The European Union has recognized the importance of an efficient and harmonized procedure for ships arriving in and/or departing from ports by adopting a range of legal instruments aimed at reducing administrative barriers for ships arriving in and/or departing from European ports. This paper especially analyzes the solutions of Directive 2010/65/EU of the European Parliament and of the Council on the official application procedure on reporting formalities for ships arriving in and/or departing from the Member States ports and repealing Directive 2002/6/EC. It also analyses Regulation (EU) 2019/1239 of the European Parliament and of the Council on establishing a European Maritime Single Window environment and repealing Directive 2010/65/EU. The reasons for the adoption of Regulation (EU) 2019/1239 shall be specifically explained. In the last part of the paper, the authors review the achievements of the Republic of Croatia in implementing measures for establishing a single national Window. By comparing the solutions contained in EU regulations and Croatian by-laws, the authors point to the existence of non-compliance and to the need for further action.